2020
DOI: 10.1038/s41598-020-66021-w
|View full text |Cite
|
Sign up to set email alerts
|

Functional shell matrix proteins tentatively identified by asymmetric snail shell morphology

Abstract: Molluscan shell matrix proteins (SMPs) are essential in biomineralization. Here, we identify potentially important SMPs by exploiting the asymmetric shell growth in snail, Lymnaea stagnalis. Asymmetric shells require bilaterally asymmetric expression of SMP genes. We examined expression levels of 35,951 transcripts expressed in the left and right sides of mantle tissue of the pond snail, Lymnaea stagnalis. This transcriptome dataset was used to identify 207 SMPs by LC-MS/MS. 32 of the 207 SMP genes show asymme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Although the ORF was only detected in the EcMPs of A. hians , a contig (DN73320_c0_g1_i1_fr4) matching the first half of the 123 amino acids (99%) and a contig (DN41781_c0_g1_i1_fr1) matching the second half of the 82 amino acids (98%) were obtained from the transcriptome of A. argo . Although in this study we only found homologous sequences with a similar domain structure in Pinctada fucata (Matsuura et al 2018), the presence of the Pif-like/Laminin G3 protein in the shell matrix were also reported from the nautilus (Setiamarga et al 2020), a pectinid bivalve Argopecten purpuratus (Li et al 2018), and the pond snail Lymnaea stagnalis (Ishikawa et al 2020).…”
Section: Resultsmentioning
confidence: 68%
“…Although the ORF was only detected in the EcMPs of A. hians , a contig (DN73320_c0_g1_i1_fr4) matching the first half of the 123 amino acids (99%) and a contig (DN41781_c0_g1_i1_fr1) matching the second half of the 82 amino acids (98%) were obtained from the transcriptome of A. argo . Although in this study we only found homologous sequences with a similar domain structure in Pinctada fucata (Matsuura et al 2018), the presence of the Pif-like/Laminin G3 protein in the shell matrix were also reported from the nautilus (Setiamarga et al 2020), a pectinid bivalve Argopecten purpuratus (Li et al 2018), and the pond snail Lymnaea stagnalis (Ishikawa et al 2020).…”
Section: Resultsmentioning
confidence: 68%
“…8 A , Supplementary Material online, clade labeled PIF). The second homolog of Pif in the A. granulata genome, g24110, codes for a protein that is “PIF-like.” A “PIF-like” protein in Lymnaea stagnalis is associated with shell biomineralization ( Ishikawa et al. 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…These peptides have different roles in biomineralization: PIF80 binds nacre and aids in nacre formation (Suzuki et al 2009), whereas PIF97 binds to chitin and guides the growth of calcium carbonate crystals (Suzuki et al 2013). A recent study in the gastropod Lymnaea stagnalis identified a PIF-like protein that does not promote nacre production, but is expressed in tissues that suggest this PIF protein still plays a role in shell biomineralization (Ishikawa et al 2020). We found that A. granulata possesses a Pif homolog, but appears to only produce PIF97 rather than two separate peptides.…”
Section: Resultsmentioning
confidence: 99%